Delayed Manifestations of Laparoscopic Bowel Injury. Issue 5 (May 2015) - Cassaro, Sebastiano
Bowel injury (BI) is a complication of open and laparoscopic abdominal surgery associated with increased morbidity and mortality. If BI is missed at the time it occurs, it can have devastating consequences. Electrosurgery is used extensively in laparoscopic surgery and can cause thermal injuries that are harder to detect than mechanical injuries and may evolve over time. The medical literature of the past 10 years was searched for large series and compilation studies reporting overall incidence of and mortality from BI in laparoscopy, and the results of seven relevant articles, which included over 300, 000 procedures, were analyzed and tabulated. The literature was then reviewed for additional information about the specific incidence and outcome of missed BI and the role of electrosurgical thermal sources in causing BI. BI is underreported, frequently missed at surgery, and results in significant morbidity and mortality that can be ground for malpractice claims against the surgeon. Thermal injury from electrosurgical instruments may be involved in a number of injuries in laparoscopic surgery. Nearly undetectable partial-thickness thermal injury may play a role in the atypical and delayed presentation of some cases of BI.